Global Analysis of Neuronal Phosphoproteome Regulation by Chondroitin Sulfate Proteoglycans - Yu, Panpan (Public Library of Science, 2013)
Chondroitin sulfate proteoglycans (CSPGs) are major components of the extracellular matrix which mediate inhibition of axonal regeneration after injury to the central nervous system (CNS). Several neuronal receptors for CSPGs have recently been identified; however, the signaling pathways by which CSPGs restrict axonal growth are still largely unknown. In this study, we applied quantitative phosphoproteomics to investigate the global changes in protein phosphorylation induced by CSPGs in primary neurons. In combination with isobaric Tags for Relative and Absolute Quantitation (iTRAQ) labeling, strong cation exchange chromatography (SCX) fractionation, immobilized metal affinity chromatography (IMAC) and LC-MS/MS, we identified and quantified 2214 unique phosphopeptides corresponding to 1118 phosphoproteins, with 118 changing significantly in abundance with CSPG treatment. The proteins that were regulated by CSPGs included key components of synaptic vesicle trafficking, axon guidance mediated by semaphorins, integrin signaling, cadherin signaling and EGF receptor signaling pathways. A significant number of the regulated proteins are cytoskeletal and related proteins that have been implicated in regulating neurite growth. Another highly represented protein category regulated by CSPGs is nucleic acid binding proteins involved in RNA post-transcriptional regulation. Together, by screening the overall phosphoproteome changes induced by CSPGs, this data expand our understanding of CSPG signaling, which provides new insights into development of strategies for overcoming CSPG inhibition and promoting axonal regeneration after CNS injury.